Awareness of venous thromboembolism among patients with cancer: Preliminary findings from a global initiative for World Thrombosis Day. (21st October 2022) - Potere, Nicola; Barco, Stefano; Mahé, Isabelle; Cesarman‐Maus, Gabriela; Angchaisuksiri, Pantep; Leader, Avi; Okoye, Helen C.; Olayemi, Edeghonghon; Ay, Cihan; Carrier, Marc; Connors, Jean Marie; Farmakis, Ioannis T.; et al.
Abstract: Background: Cancer‐associated venous thromboembolism (CAT) has detrimental impact on patients' clinical outcomes and quality of life. Data on CAT education, communication, and awareness among the general cancer population are scanty. Methods: We present the preliminary results of an ongoing patient‐centered survey including 27 items covering major spheres of CAT. The survey, available in 14 languages, was promoted and disseminated online through social networks, email newsletters, websites, and media. Results: As of September 20, 2022, 749 participants from 27 countries completed the survey. Overall, 61.8% ( n  = 460) of responders were not aware of their risk of CAT. Among those who received information on CAT, 26.2% ( n  = 56) were informed only at the time of CAT diagnosis. Over two thirds (69.1%, n  = 501) of participants received no education on signs and symptoms of venous thromboembolism (VTE); among those who were educated about the possible clinical manifestations, 58.9% ( n  = 119) were given instructions to seek consultation in case of VTE suspicion. Two hundred twenty‐four respondents (30.9%) had a chance to discuss the potential use of primary thromboprophylaxis with health‐care providers. Just over half (58.7%, n  = 309) were unaware of the risks of bleeding associated with anticoagulation, despite being involved in anticoagulant‐related discussions or exposed to anticoagulants. Most responders (85%, n  = 612) valued receiving CAT education as highly relevant; however, 51.7% ( n  = 375) expressed concerns about insufficient time spent and clarity of education received. Conclusions: This ongoing survey involving cancer patients with diverse ethnic, cultural, and geographical backgrounds highlights important patient knowledge gaps. These findings warrant urgent interventions to improve education and awareness, and reduce CAT burden.